The Effectiveness and Efficiency of Budget Realization Performance Based on Incremental Budgeting in Lebung Gajah Village, Palembang - Bella Anggraini; Lukita Tripermata; Vhika Meiriasari (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to determine and analyze the level of efficiency and effectiveness as well as the effect of processing village funds in Lebung Gajah Urban Village, Palembang based on Incremental Budgeting. The type of research in this research was descriptive quantitative research, namely analyzing financial data, spending and budget realization using efficiency and effectiveness ratios, and analyzing data documentation by measuring expenditure in Lebung Gajah Palembang Village. The results show that the budget based on Incremental Budgeting don’t have a positive and significant effect on the effectiveness and budget realization reports in Lebung Gajah Urban Village, Palembang which was indicated by the results of the effectiveness ratio and efficiency ratio. The results of this study are expected to provide benefits for Lebung Gajah Urban Village, Palembang to improve the performance of budget realization based on budget increases.